Outcome of horizontal strabismus surgery and parents’ satisfaction - Sharma, Ananda K; Thapa, Madhu; Shrestha, Gulshan B; Sitaula, Sanjeeta; Shrestha, Gauri S (Nepalese Journal of Ophthalmology, 2014)
Introduction: A clinical audit of strabismus surgery in children in terms of functional and cosmetic outcomes helps improve the quality of services in pediatric ophthalmology.  Objective: To evaluate the outcome of strabismus surgery and assess the satisfaction of the patients’ parents with respect to the surgery outcome.Subjects and methods: A study of an interventional series of cases that included 60 strabismic subjects was carried out. The bilateral strabismus surgery under general anesthesia was performed on all subjects using the fornix approach. The parents’ understanding about strabismus and the cosmetic outcome was assessed through a set of interview questionnaires. The main outcome measures were the amount of deviation, the parents’ knowledge about strabismus and their satisfaction after the intervention. Results: Of the 60 subjects, 32 (53.3%) were esotropic and 28 (46.7%) exotropic. The male to female ratio was 1:1. The mean age with standard deviation was 16.6±8.5years,with a range of 3 to 35 years. The pre- operative mean esotropia with standard deviation was 48.2±14.8 pd, with a range of 22 to 114 pd). The pre-operative mean exotropia was 57.8±14.2 pd, with a range of 25 to 90 pd). In 93.47% of the subjects, the ocular deviation after surgery reduced significantly (p=